Natural Disasters, Globalization, Financial Development and Income Inequality in Iran - Fateh Habibi; Vahid Azizi; Salaheddin Manochehri; Parvin Ali Moradi Afshar (پژوهش‌های برنامه و توسعه)
This study investigates the impact of natural disasters on income inequality in Iran from 1980 to 2021. It also explores the moderating effects of financial development and globalization on this relationship. The Non-linear Autoregressive Distributed Lag (NARDL) method is employed for the analysis.The findings reveal that several factors influence income inequality (measured by the Gini coefficient) in both the short and long term. Positive and significant effects were observed for GDP, inflation, severe natural disasters, and the globalization index. Conversely, education level, the square of GDP (indicating an inverted U-shaped relationship), and the financial development index exhibited negative and significant effects.These results support Kuznets' hypothesis, suggesting that income inequality initially rises with economic growth (GDP) before ultimately declining. Furthermore, the study confirms an asymmetric effect of financial development and globalization on income inequality. The analysis suggests that an increase in severe natural disasters, globalization, and a decrease in financial development all contribute to rising income inequality in Iran.